A novel model to analyze Darcy Forchheimer nanofluid flow in a permeable medium with Entropy generation analysis. Issue 1 (1st January 2020) - Tlili, Iskander; Shahmir, Nazia; Ramzan, Muhammad; Kadry, Seifedine; Kim, Jung-Yeon; Nam, Yunyoung; Lu, Dianchen
Abstract : A novel mathematical model is envisaged to scrutinize the Darcy Forchheimer 3D Powell Eyring nanofluid flow in a porous medium. Flow is taken under the influence of zero mass flux and convective boundary conditions at the surface and a chemical reaction in the mass equation. The heat transfer flow is scrutinized with non-linear thermal radiation. Entropy generation analysis of the envisioned model is also conducted. The Homotopy Analysis method to yield the series solutions for the envisioned model. The graphs are plotted to witness the characteristics of several parameters versus velocity, heat, and mass distributions and are well cogitated accordingly. The findings show that the velocity is decreasing the function of Darcy-Forchheimer number. Further, the Biot number large values boost the fluid temperature. The outcomes obtained in the analysis are substantiated when compared with a published result in the literature. An outstanding matching is achieved in this regard.